Effect of multimedia in teaching Science at secondary level - Dahal, Bishnu Kumar (Siddhajyoti Interdisciplinary Journal, 2021)
The aim of this study was to investigate the effect of multimedia in teaching Science at Secondary School and attitudes toward Information and Communication Technology (ICT). The study was an experimental research design with two groups employing a pre-test and post-test. The sample schools were two public secondary school of Lalitpur district. Participants were 68 students from grade 10 studying Science from two schools. Furthermore, five science teachers in that school were also taken as samples for an interview session. The data were analyzed through statistical devices, such as mean, standard deviation, variance, t-test and chi-square test. The differences between means were computed by using two tailed t-test at 0.05 level of significance. The results indicated that the mean achievement of the group using multimedia projector was significantly better than the group without using multimedia projector. The findings of this study therefore provided strong evidence to support the use of ICT, particularly multimedia technology, in the teaching and learning of Science among secondary school students. Furthermore, the results also showed that the secondary level science teachers have positive attitude towards ICT in teaching science in the classroom.